(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
The paper tests for the existence of hysteresis in the net export development patterns of five EU member countries - the Czech Republic, Latvia, Hungary, Slovakia and Slovenia. Based on the quarterly data samples from 1996q1 to 2017q2, country-specific estimates are obtained and tested. Time series estimates point to the fractionally integrated series of net exports for the Czech Republic and Latvia, while the net exports of Hungary, Slovakia and Slovenia are best explained by SETAR (1) model specification. The research results indicate long memory property in the net export series for the Czech Republic and Latvia, thus supporting the existence of hysteresis. The net export dynamics of Hungary, Slovakia and Slovenia are found to be nonlinear and threshold dependent but still slightly different. The paper also found heterogeneity in the dynamics and properties of net exports for the countries examined in this paper. Furthermore, the paper showed an indicative similarity in the change of the contemporary net export development patterns in the sample countries.